Interreligious Environmentalism: The Way Ahmadiyya Group Engages to Interfaith Dialogue - Khalil Muflih, Miftha (Jurnal Dialog, 2023)
There have been many studies on Ahmadiyya and their involvement in inter/intra-religious dialogue. However, some of these studies only look at how the dialogue takes shape or tends to be formal. Ahmadiyya, which is a vulnerable religious group, certainly needs a new model of dialogue or encounter. This article assumes that "mutual collaboration in public issues" can be an encounter space for interfaith dialogue for religious groups, especially for minorities. From this, this research aims to see the strategy of the Ahmadiyya community in Yogyakarta to be able to engage with society and also see the inter/intra-religious dialogue model used by the Ahmadiyya community in Yogyakarta. To answer these questions, this research uses qualitative research methods. Furthermore, this research takes data through the interview process and literature obtained from Ahmadiyya online media and then analyzed using descriptive and interpretive analysis techniques. This study found that the Ahmadiyya community uses environmental issues to have dialogue with other religious communities and become a space for encounter and acceptance in society.